Komparasi Model Pembelajaran Konstruktivis Metakognitif Dan Konstruktivis Novick Terhadap Berpikir Kritis Ditinjau Dari Kemampuan Akademik - Prayitno, Baskoro Adi; Sugiharto, Bowo (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
The purpose of this study was to investigate, (1) the influence of constructivist metacognitive model compared to constructivist novick, and conventional model toward critical thinking, (2) the influence of academic achievement toward critical thinking, and (3) interaction of learning model and academic achievement toward critical thinking. The sample of this study consisted of 102 eleventh grade student from 3 state senior high schools in Surakarta. The method used in this study is a quasi-experimental research Pretest-Posttest, Non-Equivalent Control Group Design. Anacova was used to analyze the data. Critical thinking test was administered to the experimental and the control group as pre and post-tests to measure the critical thinking. The result showed that, (1) constructivist metacognitive and constructivist novick are not significantly different but those are significantly different from the conventional model toward critical thinking, (2) Upper academic students have higher critical thinking than lower academic students, (3) There is not interaction of learning model and academic achievement toward critical thinking